Krishi Vigyan Kendras Glorious Journey of Five Decades - Gautam, U S; Singh, Ranjay K; Kumar, Arvind (Indian Farming, 2024)
This article offers an insightful exploration into the evolution and transformative impact of Krishi Vigyan Kendras (KVKs) over the past fifty years. The article delves into the pivotal role of KVKs as frontline extension systems in India's agricultural landscape. It traces the inception of KVKs in 1974 and highlights their remarkable growth, with 731 KVKs currently operating across the country. The article outlines the diverse mandates of KVKs, from training and frontline demonstrations to technology assessment and capacity development, reflecting their evolution into comprehensive agricultural knowledge and resource centres. Through an analysis of significant achievements, including the adoption of innovative initiatives like Cluster Frontline Demonstrations and District Agriculture Contingency Plans, the article emphasizes the substantial impact of KVKs on enhancing agricultural productivity, sustainability, and farmers' livelihoods. Furthermore, the article highlights the challenges faced by KVKs, including workforce constraints and administrative issues, calling for concerted efforts to address these challenges and strengthen the capacity of KVKs. In conclusion, the article asserts the pivotal role of KVKs in driving inclusive and resilient agricultural development and underscores the need for sustained support and innovation to ensure their continued success in the future.